2020 Padua Muscle Days: Thirty years of translational research in Mobility Medicine - Ugo Carraro (PAGEPress Publications, 2020)
More that half-century of skeletal muscle research is continuing at the Padua University (Italy) under the auspices of the Interdepartmental Research Centre of Myology (CIR-Myo), the European Journal of Translational Myology (EJTM) and recently also with the support of the A&C M-C Foundation for Translational Myology, Padova, Italy. The Volume 30 (1), 2020 of EJTM opens with the collection of abstracts of the conference "2020 Padua Muscle Days: Mobility Medicine 30 years of Translational Research", an International Conference, that will be held March 18-21, 2020 in Euganei Hills and Padova (Italy). These abstracts are excellent examples of translational research and of the multidimensional approaches that are needed to classify and manage in both the acute and chronic phases Mobility Medicine diseases that span from neurologic, metabolic, traumatic syndromes to the biological process of aging. Their excellent contents grant the high scientific profiles of researchers and clinicians who are eager to present their results at the PaduaMuscleDays. A series of EJTM Communications will add to this preliminary evidence.   Here you can find the Announcement details.